2008
DOI: 10.1021/ma071807f
|View full text |Cite
|
Sign up to set email alerts
|

Rheo-NMR of Wormlike Micelles Formed from Nonionic Pluronic Surfactants

Abstract: Using a range of techniques combining rheology and magnetic resonance, we here investigate the flow and alignment properties of wormlike micelles formed by a 5% w/w solution of the BASF difunctional block copolymer nonionic surfactant, Pluronic P105 in water along with 4.3% w/v 1-phenylethanol-d 5 . A variety of shear-banding and alignment behaviors are observed, along with both stable and fluctuating flows. These strongly depend upon both temperature and applied shear rate. The deuterium-labelled alcohol enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…The first direct MRI observation of this type concerned micellar solutions Callaghan 1997a,b, 1999). This was afterwards confirmed by similar tests in Couette cells (Douglass et al 2008), but later, more sophisticated NMR measurements showed that shear-banding fluctuations (Lopez-Gonzalez et al 2006, Al-kaby et al 2018 and exchanges between coexisting phases (Medronho et al 2011) also occur, in keeping with observations with other techniques (Fardin and Lerouge 2012).…”
Section: R Rsupporting
confidence: 57%
“…The first direct MRI observation of this type concerned micellar solutions Callaghan 1997a,b, 1999). This was afterwards confirmed by similar tests in Couette cells (Douglass et al 2008), but later, more sophisticated NMR measurements showed that shear-banding fluctuations (Lopez-Gonzalez et al 2006, Al-kaby et al 2018 and exchanges between coexisting phases (Medronho et al 2011) also occur, in keeping with observations with other techniques (Fardin and Lerouge 2012).…”
Section: R Rsupporting
confidence: 57%
“…In these systems shear can induce breakage of the constitutive chains as well as alignment [11][12][13][14][15][16] , which both contribute to the stress relaxation required for strong shear thinning. Breakage and alignment also play important roles in shear-banding hydrogenbonded supramolecular polymers 17 , while shear-banding in dispersions of actin filaments 18 and block-copolymer wormlike micelles 19,20 is caused by alignment and shear-banding in associative polymer networks 21 is caused by breakage. Whether shearbanding is a generic phenomenon for the more common case of entangled polymeric systems is still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…The origins of a declining stress in the stress/shear rate curve are believed to be associated with the formation of shear‐induced structures. The plateau on the flow curve, which is indicative of a ‘shear‐banding’ phenomenon in which two different viscosity states of the same solution can coexist, was found to be a characteristic feature of wormlike micellar nonlinear rheology, a shear‐induced phase transition from isotropic to nematic phase, wall slip and shear stress fluctuations . Stress fluctuations have been found for a variety of micelle systems associated with the growth and destruction of the shear induced in shear‐thickening systems.…”
Section: Rheological Propertiesmentioning
confidence: 97%